Pengembangan Bahan Ajar Multimoda Transportasi Prodi Diploma Iv Transportasi Laut - Bugi Nugraha (Jurnal Syntax Admiration, 2023)
The development of teaching materials in this study refers to the ADDIE development model. explained the development of the ADDIE model includes five steps, namely: Analysis, Design, Development, Implementation, and Evaluation. The type of data used is quantitative. Data collection is done by means of a questionnaire to determine the level of eligibility of teaching materials. The results of the study showed the feasibility of the Multimodal Transportation Teaching Material product developed which was declared fit for use according to media and material experts with a percentage of 86.59% and 74.39%, According to the cadets' responses, the user response was declared feasible with a percentage of 76.12% so that the product that had been developed was suitable for use as a learning resource in the learning process of the Multimodal Transportation course.